SEGMENTAL FRACTURE OF THE CLAVICLE - UNCONVENTIONAL FRACTURE PATTERN OF A CONVENTIONALLY FRACTURED BONE: A CASE REPORT WITH REVIEW OF LITERATURE - Mohapatra, Ashutosh; Arora, Yuvraj; Choudhury, Priyam; Jangir, Rajat (Journal of Ayub Medical College Abbottabad, 2022)
Though clavicle fractures are routinely seen in clinical practice, rarely do we encounter segmental fractures. This unusual pattern of fracture in clavicle has been seldom reported previously. We present a case of segmental fracture of the left clavicle fracture in a 64year old who was treated successfully. A detailed literature review has been presented too.